Combined iodine-125 seed strand, portal vein stent, transarterial chemoembolization, lenvatinib and anti-PD-1 antibodies therapy for hepatocellular carcinoma and Vp4 portal vein tumor thrombus: A propensity-score analysis - Zhang, Zi-Han; Hou, Si-Nan; Yu, Jia-Ze; Zhang, Wen; Ma, Jing-Qin; Yang, Min-Jie; Liu, Qing-Xin; Liu, Ling-Xiao; Luo, Jian-Jun; Qu, Xu-Dong; Yan, Zhi-Ping (Frontiers in Oncology, 2023)
Objective: To evaluate the safety and efficacy of interventional therapy (iodine-125[125I] seed strand and portal vein stent [PVS] implantation plus transarterial chemoembolization [TACE]) combined with systemic therapy (lenvatinib plus anti-PD-1 antibody) as first-line treatment for hepatocellular carcinoma (HCC) patients with Vp4 portal vein tumor thrombus (PVTT). Patients and Methods: From December 2018 to October 2021, 87 HCC patients with Vp4 PVTT were included in this single-center retrospective study. Forty-seven patients underwent interventional therapy combined with lenvatinib and anti-PD-1 antibody (group A), while 40 cases underwent interventional therapy combined with lenvatinib only (group B). Overall response rate (ORR), stent occlusion rates (SOR), median overall survival (OS), median progression-free survival (PFS) and median stent patency time (SPT) were compared between the 2 groups. Results: The mean intended dose (r = 10 mm; z = 0; 240 days) was 64.9 ± 1.0 Gy and 64.5 ± 1.1 Gy in group A and B, respectively (p = 0.133). ORR and SOR were significantly different between group A and B (ORR, 55.3% vs 17.5%, p < 0.001; SOR, 12.8% vs 35.0%, p = 0.014). In the propensity-score matching (PSM) cohort, the median OS, median PFS and median SPT were significantly longer in group A compared with group B (32 PSM pairs; OS, 17.7 ± 1.7 vs 12.0 ± 0.8 months, p = 0.010; PFS, 17.0 ± 4.3 vs 8.0 ± 0.7 months, p < 0.001; SPT, not-reached vs 12.5 ± 1.1 months, p = 0.028). Conclusion: This interventional therapy combined with lenvatinib and anti-PD-1 antibody is safe and effective for HCC patients with Vp4 PVTT.